Etika Pemimpin Politik Dalam Islam dan Langkah Pencegahan Pelanggaran Etika - Iskandar, Nurul Hikmah Ramadhani; Kadri, Muh. Fajrin; Ramadhan, Mohammad Sahrial (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The ethics of political leaders is the main problem that occurs in political practice. It is also important for everyone to understand the ethics of political leaders so that political life can run fairly and with quality. Therefore, studies are needed to address or overcome the ethics of political leaders as an important factor or figure in a government. This research aims to find out more about the ethics of political leadership from an Islamic perspective and efforts to prevent ethical violations. Apart from that, the research method used is a descriptive analysis method through written sources such as journals, books and other sources. The findings from this research are biased towards the leadership traits of the Prophet who became an example to his people, namely: honesty, trustworthiness, fathonah (intelligent), and tabligh. And also the political ethics that were applied during the time of the caliph Salahuddin Al-Ayyubi, as well as the views of ulama on several ethical criteria that need to be present in a leader. In line with that, it also provides an example of one of the regions in Indonesia that implemented Islamic law during the kingdom period which provided for the application of law in accordance with Islamic teachings or Islamic principles. This is then continued with efforts to prevent violations of leadership ethics according to Islam, namely providing training and education, establishing a code of ethics, public supervision and transparency, with the aim that everyone will set an example to lead to prosperity and benefit. Therefore, this research was created to increase everyone's understanding regarding leader ethics from an Islamic perspective.